Peran Kepemimpinan Kepala Sekolah Dalam Peningkatan Kinerja Guru Di SMA Negeri 2 Makassar - Gita Irawanda; Ansar Ansar (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2021)
This study examines the role of the principal's leadership in enhancement teacher performance at SMA Negeri 2 Makassar. The purpose of this study was to determine 1) the leadership role of the principal in enhancement teacher performance at SMA Negeri 2 Makassar; 2) the supporting and inhibiting factors of the principal's leadership role in enhancement teacher performance at SMA Negeri 2 Makassar. This type of research is qualitative with a descriptive approach. The results showed that the principal's leadership in enhancement teacher performance was through his role as a) educators, conduct various activities to improve teacher competence in schools, such as in-house training and development workshops and become resource persons in these activities; b) managers, carry out development workshops, conduct in-house training, carry out MGMP activities inside and outside the school, and involve teachers in training activities; c) administrators, making strategic programs to improve teacher professionalism and supervising the implementation of learning; d) supervisors, supervise learning and study lesson plans, conduct individual meetings and follow up on the results of supervision, as well as provide support for facilities and a conducive atmosphere;   e) leader (leader), arouse the enthusiasm and cooperation of teachers, increase teacher interest in the development of education and implement multi-directional communication: f) motivators; provide verbal motivation and rewards, manage the school's physical environment, work atmosphere and discipline and provide learning resources; g) innovators, directing teachers to apply innovative learning models, create new ideas and integrate activities. Supporting factors, namely the support of adequate learning facilities, a conducive environment and the provision of rewards and reprimands, then the inhibiting factor, namely school principals find it quite difficult to change the mindset of teachers who are beyond productive age in following technological developments.